Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Kontrak Menggunakan Metode Multy Attribute Utlity Theory (MAUT) (Studi Kasus : PT. Telkom Marisa) - Muhammad Isla; Almer Hassan Ali (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
Performance appraisal of contract employees at PT. Telkom Marisa has notbeenimplemented optimally, especially in assessing the performance of contract employees. So far, the assessment of contract employees is only determined from the results of their work, there are no clear assessment criteria. Therefore, in this study, a performance appraisal of contract employees will be developed based on competencies that are expected to be able to accommodate the performance of contract employees. Employee performance appraisal consists of 5 (five) competencies, namely Discipline, Cooperation, Integrity, Responsibility, Leadership. by using the multi attribute utility theory (MAUT) method. The aim of this research is to create a decision support system to assess the performance of contract employees at PT. Telkom Marisa using the multi attribute utility theory (MAUT) method so that it can assess the performance of contract employees and display recommendations for employees who have the best performance.Keywords: Performance, Competence, PT. Telkom Marisa, Recommendations, multi attribute utility theory (MAUT)